Auditor independence, CSR, and carbon risk in shaping earnings management: Moderation by good corporate governance - Tamara Dian Puspitawati; Catur Ragil Sutrisno; Dina Amalia Mahmudah (Universitas Pekalongan, 2026)
This study examines the relationship between auditor independence, corporate social responsibility (CSR), and carbon risk on earnings management, with good corporate governance (GCG) serving as a moderating variable. The research focuses on consumer non-cyclical companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Using a purposive sampling technique, the final sample consists of firms that consistently published annual and sustainability reports throughout the observation period. Data analysis is conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM), supported by WarpPLS 7.0 software. The empirical findings reveal that auditor independence does not significantly influence earnings management practices. In contrast, corporate social responsibility is found to have a negative effect on earnings management, indicating that firms with stronger CSR engagement tend to exhibit lower levels of earnings manipulation. Meanwhile, carbon risk shows a positive and significant effect on earnings management, suggesting that higher exposure to carbon-related risks encourages managerial discretion in financial reporting. Furthermore, the moderating analysis demonstrates that good corporate governance does not moderate the relationship between auditor independence and earnings management, nor does it moderate the effect of carbon risk. However, good corporate governance strengthens the negative relationship between corporate social responsibility and earnings management. These findings contribute to the literature by highlighting the role of sustainability-related factors and governance mechanisms in shaping earnings management behavior. Practically, the results emphasize the importance of effective governance structures and CSR implementation in enhancing financial reporting quality.